Effect of CTOP on Behavioural Intentions in the Banking Sector: The Mediation Role of Trust - Banahene, Stephen (Advances in Social Sciences Research Journal, 2018)
The issue of service quality measurement is extensively researched, but the continuous changing banking regulatory environment necessitates a correspondingly continuous evaluation of service quality factors. This study uses CTOP (customer care, tangible value, operational value and product value) to measure service quality in the banking sector, and investigated its effect on customer behavioural intentions with trust as a mediator. The study was conducted on 825 useable responses which represented 82.5% of questionnaires distributed. Explanatory research design was used and Stata version 13 and IBM Statistical Package for Social Sciences version 20 were the software used in data analysis. The study used Structural Equation Model (SEM) for data analysis and explored direct, indirect and total effect relationships. Confirmatory Factor Analysis (CFA) was used for data purification. The research found that CTOP has positive and statistical significant relationships with customer trust and customer behavioural intentions. Customer trust also has positive and statistical significant relationship with customer behavioural intentions. On the mediation effect, customer trust partially mediates between CTOP and customer behavioural intentions. Customer trust fully mediates between product and tangible values on one hand and customer behavioural intentions on the other. Product value affects customer intentionality and in turn intentionality also affect customer advocacy. This means that researchers and managers of banks should consider CTOP effects on customer behavioural intentions with or without customer trust. However, researchers and service firm managers should note that for product and tangible values to affect customer behavioural intentions, trust must be considered.